Flooding and planting density shape forests in an experimental Everglades landscape: Lessons for forest restoration. Issue 9 (8th September 2022) - Stoffella, Susana L.; Ross, Michael S.; Sah, Jay P.; Price, René M.; Scinto, Leonard J.; Cline, Eric A.; Sklar, Fred H.
Abstract: Tree islands, a prominent feature of wetland landscapes worldwide, are patches of forest scattered throughout a matrix of herbaceous marsh. In the Florida Everglades, their development over millennia as elevated, relatively well‐drained features above the wetland surface has made them cultural centers for indigenous people and refugia for a rich assortment of plants and animals. However, since the early years of the twentieth century, the number and area of tree islands have been roughly halved in Everglades National Park and Water Conservation Areas due to scarce or excessive water levels, leading to fires or persistent flooding, respectively. This loss has prompted a need for tree island rehabilitation or reconstruction within the ongoing state–federal partnership to bring about Everglades restoration. In this paper, we present results of a field‐scale experiment that examined the effects of flooding, planting density, and the size and proximity of neighbors on the performance of native tree species on constructed tree islands. Hypotheses derived using the stress‐gradient hypothesis as a framework were tested at the neighborhood level. Flooding reduced survival and mean tree size 7–8 years after initial planting, while planting seedlings at spacings as close as 1 m apart resulted in higher total biomass, with no significant cost in tree survival. Flood‐tolerant species increased in relative abundance during the study period along the entire hydrologic gradient, while flood‐intolerant species were able to survive only at higher elevations. Crowding effects within neighborhoods varied across the flooding gradient. Survival increased or remained stable as neighbor effects increased in high‐flooding zones, while declining sharply as crowding increased under low‐flooding conditions. Similar results were obtained for the growth of flood‐tolerant species under close spacing, with most showing an increment in growth where flooding was high. These data suggest that tree island restoration can benefit from targeted mixed‐species plantings at variable densities, as the compositional and structural heterogeneity promoted by these measures may increase adaptability and resilience to future uncertainties.